Hydrochemistry and Environmental Isotope Characteristics of Groundwater in the Kashgar Delta Area, Xinjiang, China - Wei Xing; Zhou Jinlong; Zhou Yinzhu; Zeng Yanyan; Chen Yunfei (E3S Web of Conferences, 2019)
The hydrochemistry and isotope characteristics of groundwater of different geomorphological types in the Kashgar Delta in Xinjiang, China were studied using isotopic analyses. Results showed that groundwater in the study area was mainly recharged by precipitation, and that groundwater ions were mainly affected by weathering-leaching of rock salt and evaporite as well as cation exchange and adsorption. The hydrochemical type of phreatic water in the alluvial-proluvial gravel plain on the piedmont slope was mainly SO4·Cl-Na·Ca type, with an average age of 28a. The phreatic water in the fluvial plain had shallow buried depth and intense evaporation. The hydrochemical type of phreatic water varied from SO4·Cl-Na·Mg type to Cl-Na type, with an average age of 99a. Along the groundwater flow path eastward, confined water in the fluvial plain experienced gradually more intense cation exchange and stronger adsorption. The major hydrochemical type of which was the SO4·Cl-Na type, with an average age of 30405a.